CURRENT PERSPECTIVES ON THE USE OF ARTIFICIAL INTELLIGENCE IN MEDICAL EDUCATION - Zarnigor Obidovna, Djalilova (Prospects for innovative technologies in science and education, 2024)
The use of artificial intelligence (AI) in medical education is transforming traditional teaching methodologies by providing innovative tools to enhance learning, assessment, and clinical training. AI technologies such as adaptive learning systems, virtual simulations, and natural language processing improve the understanding of complex medical concepts, foster critical thinking, and facilitate personalized education. These advancements allow medical students to develop diagnostic and decision-making skills in realistic scenarios, bridging the gap between theory and practice. Despite its potential, integrating AI into medical education requires addressing challenges such as ethical concerns, data privacy, and equitable access. This study explores the current applications of AI in medical education, highlighting its benefits and future implications for the field.